Abdominal wall abscess after cholecystectomy - Grass, Fabian (BMC Res Notes, 2015)
BACKGROUND: Laparoscopic cholecystectomy is one of the most frequently performed surgical interventions nowadays in developed countries. While lost gallstones during the procedure represent a commonly encountered issue, there is an ongoing debate whether split gallstones imperatively need to be extracted during the same procedure. The reported case of a wall abscess several years after follow-up lights up this debate. CASE PRESENTATION: A 75-year-old male Caucasian with a history of rheumatoid arthritis and congestive heart failure presented with a recurrent subcutaneous abdominal wall abscess with occasional, spontaneous drainage of pus. He underwent laparoscopic cholecystectomy for acute calculous cholecystitis 3 years ago with uneventful and prompt recovery. A computed tomography scan showed a cavity in the periumbilical abdominal wall with peripheral contrast-enhancing, next to a calcified foreign body between the rectus muscle sheets. Wound exploration under general anaesthesia was performed with drainage of the cavity, extraction of the foreign body and closure of the anterior rectus sheet over a drainage catheter. The foreign body turned out to be a gallstone lost in the periumbilical port site during the procedure. Antibiotic treatment with co-amoxiclav was continued for 14 days. The patient was discharged 9 days postoperatively with a clean wound. CONCLUSION: This case and short review of the literature is a reminder of the importance of careful extraction of split gallstones during cholecystectomy in order to avoid early or late complications. This is especially important in the light of one of the most commonly performed surgical procedures in developed countries with generally low morbidity.